Characterisation of a cold atmospheric pressure plasma torch for medical applications: demonstration of device safety - Bennett, Adam; Urayama, Takuya; Papangelis, Konstantinos; Yuen, Peter W. T.; Yu, Nan (MDPI, 2021)
The safety and effectiveness of plasma devices are of crucial importance for medical applications. This study presents the novel design of an atmospheric plasma torch (SteriPlas) and its characterisation. The SteriPlas was characterised to ascertain whether it is safe for application on human skin. The emission spectrum discharged from the SteriPlas was shown to be the same as the emission from the MicroPlaSter Beta. The UV emitted from the SteriPlas was measured, and the effective irradiance was calculated. The effective irradiance enabled the determination of the maximum UV exposure limits, which were shown to be over two hours: significantly longer than the current two-minute treatment time. The use of an extraction system with a higher flow rate appears to reduce slightly the effective irradiance at the treatment area. The NOx and ozone emissions were recorded for both SteriPlas configurations. The NOx levels were shown to be orders of agnitude lower than their safety limits. The ozone emissions were shown to be safe 25 mm from the SteriPlas cage. A discussion of how safety standards differ from one regulatory body to another is given.
This article belongs to the Special Issue Gas Plasma Technology in Biology and Medicine
Keywords: cold atmospheric plasma; biological and physical characterisation; plasma medicine; ultraviolet (UV); reactive oxygen nitrogen species (RONS); wound management; anti-bacterial; plasma healthcare; safety standards